Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This question is related to an earlier post.

Suppose we have a sequence $(a_n)$ of real numbers and we are interested in the existence and value of the series \begin{equation} \lim_{N \to \infty} \qquad \sum^N_{n = 1} (a_n - a_{n-1}) \,. \end{equation} Looking at the partial sum, we have $S_N = a_N - a_0$.

Now here comes my question:

Is it always (i.e. for any sequence $(a_n)$) true that \begin{equation} \lim_{N \to \infty} \qquad \sum^N_{n = 1} (a_n - a_{n-1}) = \lim_{N \to \infty} a_N - a_0 \qquad ? \end{equation}

I am asking because in the book "Yet another Introduction to Analysis" by Victor Bryant there is the following remark, suggesting the answer to my above question is NO (not always):

If we let $S_N = \sum_{n = 1}^N (-1)^{n+1} \frac{1}{n}$ then the resulting series exists. Denote its value by $S$.

Writing the same partial sum as \begin{equation} T_N = 1 - \frac{1}{2} - \frac{1}{4} + \frac{1}{3} - \frac{1}{6} - \frac{1}{8} + \frac{1}{5} - \frac{1}{10} - \dots \text{up to } (-1)^{N+1}\frac{1}{N} \end{equation} (i.e we rearrange the terms) we have $T_{3N} = \frac{1}{2} S_{2N}$, hence

\begin{equation} T = \lim_{N \to \infty} T_N = \lim_{N \to \infty} T_{3N} = \frac{1}{2}\lim_{N \to \infty} S_{2N} = \frac{1}{2} \lim_{N \to \infty} S_N = \frac{1}{2}S \,. \end{equation}

So all we did was rearranging the summands in the partial sums before taking the limit, and it changed the value of the series.

To repeat my question:

Is it always (i.e. for any sequence $(a_n)$) true that \begin{equation} \lim_{N \to \infty} \qquad \sum^N_{n = 1} (a_n - a_{n-1}) = \lim_{N \to \infty} a_N - a_0 \qquad ? \end{equation}

Many thanks for your help!

share|cite|improve this question
up vote 1 down vote accepted

I thought I answered this at the other question. $T_N$ is not a rearrangement of $S_N$. Pick a value of $N$, and write out $S_N$, and write out $T_N$, and you will see that there are terms in the one that are not in the other.

share|cite|improve this answer
Ah! Now I understand, this is where my confusion comes from, because the example actually talks about different sequences of partial sums. I am sorry I didn't get your answer in the first place! – harlekin Jan 22 '12 at 12:13

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.